Error Estimations of Homotopy Perturbation Method for linear Integral and Integro-Differential Equations of the Third kind - Eshkuvatov Z.K; Zulkarnain F.S.; Nik Long N.M.A.; Muminov Z. (Research & Reviews, USA, 2024)
Non-Indexed Publication